2007
DOI: 10.1053/j.gastro.2007.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Translational Inhibition of Colonic Epithelial Heat Shock Proteins by IFN-γ and TNF-α in Intestinal Inflammation

Abstract: Background & Aims-Inducible heat shock proteins (iHsp), Hsp25/27 and Hsp70, play essential roles in protecting cells against stress and, in intestinal mucosal inflammation, potentially lessening the extent and severity of injury. We examined the expression and regulation of iHsp in human and experimental inflammatory bowel diseases (IBD) and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 34 publications
10
80
4
1
Order By: Relevance
“…It is interesting that down-regulation of HSP70 has been found to be associated with IBD development (Bhattacharrya et al 2009;Köken et al 2004;Hu et al 2007). Although we also reported that a 1% GTPs diet aggravated colitis in DSSexposed mice , it was not clear whether 1% GTPs affected the expression HSP70 in that model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that down-regulation of HSP70 has been found to be associated with IBD development (Bhattacharrya et al 2009;Köken et al 2004;Hu et al 2007). Although we also reported that a 1% GTPs diet aggravated colitis in DSSexposed mice , it was not clear whether 1% GTPs affected the expression HSP70 in that model.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expressions of HSP70 and HSP27 were found to be down-regulated in actively inflamed mucosa from individuals with IBD (Bhattacharrya et al 2009;Köken et al 2004). It is worth noting that the production of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin, were also found to be increased in IBD, while it down-regulated HSP70 by targeting its translation stage (Hu et al 2007). The above background suggests that inflammatory signaling molecules aggravate colitis by down-regulating HSPs, thereby disrupting intestinal homeostasis.…”
mentioning
confidence: 99%
“…Specific repression of translation of HSP mRNAs has been described in other contexts; for example under basal conditions, translation of chicken reticulocyte HSP70 mRNA is restricted through a reduced elongation rate (Theodorakis et al 1988). In addition, injection of IFN-γ and TNF-α, inflammatory factors that are also associated with H. pylori infection, were found to preferentially inhibit HSP translation without altering mRNA levels in a mouse model of colitis (Hu et al 2007). Whether H. pylori infection plays a role in specific HSP repression via a mechanism similar to the previously mentioned contexts remains to be seen.…”
Section: Discussionmentioning
confidence: 87%
“…In an animal model of colitis, injection of interferon and TNF-α activated PKR, and resulted in markedly impaired Hsp25 and Hsp70 protein synthesis at the translational level; Hsp25 and Hsp70 were in fact nearly absent in the gut mucosa, while the mRNA of these proteins remained unaffected. The authors observed that the cytokines blocked Hsp70 synthesis twice as much as they blocked β-actin, suggesting that while there is a global reduction in protein translation, Hsp70 is blocked more aggressively (Hu et al 2007). In the case of NDV, however, reduction in protein translation was more global, and not specific to Hsps.…”
Section: Herpes Simplex Virusmentioning
confidence: 99%